Carbon dots on LAPONITE® hybrid nanocomposites: solid-state emission and inter-aggregate energy transfer - Onishi, Bruno S. D. [UNESP]; Carneiro Neto, Albano N.; Bortolleto-Santos, Ricardo; Masterlaro, Valmor R.; Carlos, Luís D.; Ferreira, Rute A. S.; Ribeiro, Sidney J. L. [UNESP] (Royal Society of Chemistry (RSC), 2024)
This study delves into the photoluminescent characteristics of solid-state hybrid carbon dots/LAPONITE® (CDLP). These hybrid materials were synthesized using the hydrothermal method with a precise pH control set at 8.5. The LAPONITE® structure remains intact without structural collapse, and we detected the possible deposition of carbon dots (CDs) aggregates on the clay mineral's edges. The use of different concentrations of citric acid (10-, 6-, 2- and 1-times weight/weight of LAPONITE® mass, maintaining the 1 : 1 molar ratio with ethylenediamine) during synthesis results in different CDs concentrations in CDLP-A (low precursors concentration) and CDLP-D (high concentration) with an amorphous structure and average size around 2.8-3.0 nm. The CDLP displayed visible photoluminescence emission in aqueous and powder, which the last underwent quenching according to lifetimes and quantum yield measurements. Low-temperature measurements revealed an enhancement of the non-radiative pathways induced by aggregation. Energy transfer modelling based on Förster-Dexter suggests an approximate mean distance of 9.5 nm between clusters of CDs.